Effective use of marketing technology in Eastern Europe: Web analytics, social media, customer analytics, digital campaigns and mobile applications - Jayaram, Dureen; Manrai, Ajay K.; Manrai, Lalita A. (Universidad ESAN. ESAN Ediciones, 2015)
The transition economies of Eastern Europe present both the opportunities and challenges for companies operating in these markets. On one hand, these countries have a large number of technology savvy young consumers, and on the other, the markets must also take into consideration the macro-environment of a country and market conditions which make the use of certain market technologies more feasible and attractive compared to others. It is certainly true in terms of the timing for introduction of various technologies in a country. Drawing analogy for the “IDITAROD RACE” we develop three different “Sled Dog Team layouts” for market characteristics and technologies for three Eastern European countries, namely, Slovakia, Bulgaria, and Albania. The ten market characteristics included in our research are: digital connectivity divide, economic power, demand type, privacy laws, demographics, and competitive conditions, attitude towards technology, institutional maturity, corporate social responsibility, and corruption. The ten marketing technologies included in our research are: digital profiling, segmentation, websites, and search engines marketing, campaign management, content management, social media, mobile application, digital collaborations, and analytics. Company case studies are analyzed and reported for each of these three countries which support the three models presented in our research.

Las economías de transición de Europa Oriental presentan a la vez oportunidades y retos para las empresas que operan en dichos mercados. Por un lado, estos países cuentan con un gran número de jóvenes y expertos consumidores tecnológicos y, por otro, los mercados deben tener en cuenta el macroentorno de un país y las condiciones del mercado, que pueden facilitar el uso de ciertas tecnologías y hacerlas más atractivas en comparación con otras. Esto es realmente cierto al elegir la oportunidad para introducir diversas tecnologías en un país. Utilizando la analogía de la “CARRERA IDITAROD”, desarrollamos tres diferentes “diseños de equipos de perros de trineo” para las características del mercado y las tecnologías de tres países del este de Europa, es decir, Eslovaquia, Bulgaria y Albania. Las diez características del mercado que incluimos en nuestra investigación son: clasificación de la conectividad digital, poder económico, tipo de demanda, leyes de privacidad, características demográficas y condiciones competitivas, actitud hacia la tecnología, madurez institucional, responsabilidad social corporativa y corrupción. Las diez tecnologías de marketing incluidas en nuestro estudio son: perfil digital, segmentación, sitios web y marketing de motores de búsqueda, gestión de campañas, gestión de contenidos, medios sociales, aplicación móvil, colaboraciones digitales y analítica. Se analizan y reportan los estudios de los casos empresariales para cada uno de estos tres países, que respaldan los tres modelos presentados en nuestro trabajo de investigación.
Keywords: Three speed Eastern Europe; Slovakia; Bulgaria; Albania; Tres velocidades de Europa del Este; Eslovaquia; Iditarod Race; Bulgaria; Albania; Sled Dog Model; Carrera Iditarod; Market characteristics; Modelo de perros de trineo; Características del mercado; Marketing technologies; Tecnologías de marketing; https://purl.org/pe-repo/ocde/ford#5.02.04